Effects of Glycine and Threonine Supplementation on Performance of Broiler Chicks Fed Diets Low in Crude Protein - Waldroup, P.W.; Jiang, Q.; Fritts, C.A. (International Journal of Poultry Science, 2005)
A study was conducted to evaluate effects of dietary crude protein (CP) level and Gly and Thr supplementation on performance of male broiler chicks during the period of 0 to 21 days. Diets were formulated based on NRC (1994) recommendations (Lysine at 110% of suggested level). All diets were formulated to contain 3,200 ME kcal/kg. A minimum dietary electrolyte balance of 250 meq/kg was stipulated with a minimum of 0.25% sodium and 0.20% chloride. Five primary diets were formulated to contain 16%, 18%, 20%, 22%, and 24% CP. The diets were then supplemented with additional 0, 0.2%, 0.4% Gly or 0, 0.2%, 0.4% Thr in all possible combinations resulting in a 5x3x3 factorial arrangement. Each of the 45 treatments was fed to six replicate pens of five male commercial broilers. The test diets and tap water were provided for the ad libitum consumption from 1 to 21 d of age. At 21 d of age body weight and feed consumption were determined. Reducing dietary protein below 22% significantly reduced 21 d BW and depressed feed conversion. Addition of 0.2 or 0.4% Gly significantly improved BW and numerically improved feed conversion at lower levels of protein but at protein levels of 20% or more the basal diets appeared to provide sufficient Gly. These data suggest that requirements for Gly suggested by NRC (1994) are inadequate in diets with low CP. Thr supplementation was ineffective in improving performance at low CP levels suggesting that the present recommendations of NRC (1994) are adequate. Mortality did not vary significantly among chicks receiving all experimental diets.